Maternal Inheritance of U’s Triangle and Evolutionary Process of Brassica Mitochondrial Genomes - Xue, Jia-Yu; Wang, Yue; Chen, Min; Dong, Shanshan; Shao, Zhu-Qing; Liu, Yang (Frontiers in Plant Science, 2020)
The sequences and genomic structures of plant mitochondrial (mt) genomes provide unique material for phylogenetic studies. The nature of uni-parental inheritance renders an advantage when utilizing mt genomes for determining the parental sources of hybridized taxa. In this study, a concatenated matrix of mt genes was used to infer the phylogenetic relationships of six cultivated Brassica taxa and explore the maternal origins of three allotetraploids. The well-resolved sister relationships between two pairs of diploid and allotetraploid taxa suggest that B. carinata (car) possessed a maternal origin from B. nigra, while B. juncea (jun) was maternally derived from B. rapa (cam). Another allotetraploid taxon, B. napus (cv. Wester) may have been maternally derived from the common ancestor of B. rapa and B. oleracea (ole), and / or have undergone (an) extra hybridization event(s) along its evolutionary history. The characteristics of Brassica mt genomic structures also supported the phylogenetic results. Sinapis arvensis was nested inside the Brassica species, sister to the B. nigra-B. carinata lineage, and possessed an mt genome structure that mostly resembled B. nigra. Collectively, the evidence supported a systematic revision that placed S. arvensis within Brassica. Finally, ancestral mt genomes at each evolutionary node of Brassica were reconstructed, and the detailed and dynamic evolution of Brassica mt genomes were successfully reproduced. The mt genome of B. nigra structurally resembled that of the Brassica ancestor the most, with only one reversion of a block, and the B. oleracea underwent the most drastic changes. These findings suggested that repeat-mediated recombinations were largely responsible for the observed structural variations in the evolutionary history of Brassica mt genomes.